IDENTIFIKASI KERAGAMAN GENETIK DAERAH 3’UTR GEN LDLR PENDUDUK ASLI PAPUA - Windasari Windasari; Muhammad Fajar Islam; Achmad Taher (FMIPA Universitas Papua, 2022)
Papua is one of the big islands in Indonesia that has many tribes live within different ecological zones. Different ecological zones may potentially result in genetic diversity of their population. Researches in genetic diversity of the Native Papuans are very rare, mainly in terms of the diversity of the LDLR gen within the 3’UTR. The research aimed to identify the genetic diversity of the LDLR gen of the indigenous people of Papua within the 3’UTR. Four steps were performed in the research, namely DNA extraction, amplification, electrophoresis, and sequencing. Two SNPs within the 3’UTR’s were identified with a nucleotide diversity (π) of 0.00177. The identified SNPs are at *52, that is G>A and at *504, that is G>A. The observed haplotypes are GG and AA with a diversity of 0.533± 0.172.